Studies on the fertility and breeding management of New Zealand dairy cows : a thesis presented to Massey University as a requirement for the degree of Doctor of Science - Macmillan, K. L. (Massey University, 1982)
This thesis reviews an extensive research program on the fertility of dairy catt1e in New Zealand. Most of the work was completed between 1967 and 1977. It involved studying numerous basic aspects of reproductive physiology by analysing extensive amounts of data either lodged within a large centralised recording system, or produced through the participating cooperation of herd owners or inseminators. New concepts were developed and old recommendations sometimes found to be inappropriate.
This Doctor of Science comprises a number of published works listed in the Bibliography in the attached file. Due to copyright restriction, they are not included here but can be accessed individually from the publisher.
Keywords: Dairy cattle; New Zealand; Reproduction